2014
DOI: 10.7863/ultra.33.9.1663
|View full text |Cite
|
Sign up to set email alerts
|

Inactivation of Escherichia coli and Staphylococcus aureus by Ultrasound

Abstract: Objectives The aim of this study was to obtain valuable information about the effect of ultrasonic irradiation with a frequency of 30 kHz frequency and power of 100 W on the inactivation capability of two bacterial groups, namely, Escherichia coli ATCC 25922 and Staphylococcus aureus ATCC 25923, in physiologic water samples. Methods Ultrasonic irradiation of bacterial samples with different populations of 5 × 103, 1.5 × 104, and 3 × 104 colony‐forming units/mL was performed at a constant frequency with various… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 17 publications
(24 reference statements)
1
14
0
Order By: Relevance
“…Ultrasonication of the mixture was then carried out by a sonicator (SK3310HP, KUDOS) at 53 kHz, 180 W and 30 °C for 20 min. (Step 4) to disrupt cell membranes and release cellular contents, such as hemoglobin from the red blood cell (RBC)—so called sonoporation 36 , 37 —more thoroughly, while avoiding bacteria inactivation 38 40 . After the resultant sample tube underwent the same centrifugation procedure (Step 5), the supernatant—containing hemoglobin, cellular fragments and other low-density components, etc .—was replaced with sterile water (Step 6).…”
Section: Methodsmentioning
confidence: 99%
“…Ultrasonication of the mixture was then carried out by a sonicator (SK3310HP, KUDOS) at 53 kHz, 180 W and 30 °C for 20 min. (Step 4) to disrupt cell membranes and release cellular contents, such as hemoglobin from the red blood cell (RBC)—so called sonoporation 36 , 37 —more thoroughly, while avoiding bacteria inactivation 38 40 . After the resultant sample tube underwent the same centrifugation procedure (Step 5), the supernatant—containing hemoglobin, cellular fragments and other low-density components, etc .—was replaced with sterile water (Step 6).…”
Section: Methodsmentioning
confidence: 99%
“…Unorthodox combination of low frequency ultrasound (LFU) and antimicrobial agents may bridge the gap in current treatment against biofilm infections. As a noninvasive physical method, ultrasonic irradiation can be achieved under ambient conditions of pressure and temperature without any chemical compounds, making it one of the most attractive methods [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…The strongest treatment reduced all bacteria significantly but S. aureus was reduced only 0.55 log. Similarly, Sesal and Kekeç (2014) found that ultrasonic irradiation (30 kHz frequency and power of 100 W) is not a suitable method for the elimination of S. aureus in physiological water samples.…”
Section: Resultsmentioning
confidence: 99%